Artificial intelligence boosting food safety immunoassays: technological advances and applications - Ming-Xi He; Ri-Sheng Chen; Dong Huang; Zhen-Lin Xu; Aori Qileng (Current Opinion in Food Science, 2026)

Impact of Cultivation on Soil Phosphorus Content along the Altitude Gradient in Alpine Forest of the Tibetan Plateau - Yuxuan Cui; Xu-Ri; Fengzi Li; Songbo Qu; Ribu Shama; Lin Zhang; Eryuan Liang (Journal of Soil Science and Plant Nutrition, 2026)

Risk factors for polymicrobial klebsiella pneumoniae bloodstream infection: a retrospective cohort study using the antimicrobial resistance monitoring database - Huian Ge; Jianhao Su; Gaoxiang Xu; Yanan Li; Zhikang Xiao; Jiaqing Yan; Yigeng Peng; Jianzhong Xu; Chen Qiu; Ri Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Multidimensional dissection of shared genetic susceptibility in ulcerative colitis and colorectal cancer: novel insights from integrative single-cell and multi-omics analysis - Fanfan Zhu; Xin Yao; Da Liu; Shanshan Wang; Xuyu Huang; Jing Zhou; Song Wang; Shanneng Tang; Dongping Lai; Shuang Yang; Xiaobing Meng; Xinyue Zhang; et al. (Inflammation Research, 2026)

Multivariable genome-wide analysis elucidates the shared genetic architecture, immunosenescence features, and gut-origin therapeutic targets of ulcerative colitis-associated multisystem inflammation - Shanneng Tang; Xin Yao; Shanshan Wang; Fanfan Zhu; Wenbin Zeng; Dongping Lai; Xiaobing Meng; Xinyue Zhang; Ziming Zhu; Tao Zhang; Ri’an Xu (Inflammation Research, 2026)

Synergistic coupling of micellar confinement and interfacial adsorption for fabricating high-density spherical nickel (II) tricarbohydrazide perchlorate - Jie-xin He; Dong-xu Zhang; Feng-yi Xia; Ri-lige Su; Bo-bo Lu; Jia-ni Xie; Zi-jie Bi; Qian-you Wang; Li Yang (Chemical Engineering Journal, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

CARE: a next-generation high resolution cloud and radiation remote sensing product and its Earth system applications - Husi Letu; Huazhe Shang; Run Ma; Chong Shi; Takashi Y. Nakajima; Hiroshi Ishimoto; Jérôme Riedi; Lesi Wei; Ri Xu; Dabin Ji; Qixiang Sun; Sude Bilige; et al. (Science Bulletin, 2026)

A Deep-Learning Model for Stroke Subtype Identification in Moyamoya Disease Based on Digital Subtraction Angiography - Zhi-wen Liu; Fei Shang; Ri-Miao Yang; Cong Han; Shuai Liu; Guo-zheng Xu (Translational Stroke Research, 2026)

Temporal dynamics of microbial-soil particulate organic matter in response to nitrogen addition in an alpine steppe - Yilun Hu; Shang Wang; Qiuyu Chen; Ang Hu; Bin Niu; Xiang Chen; Ri Xu; Gengxin Zhang (Applied Soil Ecology, 2026)

Novel hapten design and highly sensitive monoclonal antibody–based immunochromatographic assay for benzo[a]pyrene in edible oil - Huan-Yuan Xu; Ri-Sheng Chen; Yu Wang; Yue-ming Chen; Sumed Yadoung; Surat Hongsibsong; Peiqiang Shuai; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

Fusaritricins E–G, three new polyketides, isolated from the endophytic fungus Fusarium sp. HC20 and their antifungal activities - Xu-Ri Wan; Chang Li; Ling-Yan Liu; Fang Yue; Xuan Lu; Yue-Hu Pei; Yi-Hui Yang (Phytochemistry Letters, 2025)

High-resolution imaging of plant delayed luminescence - Yan-Xia Liu; Hai-Yu Fan; Yu-Hao Wang; Yan-Liang Wang; Sheng-Wen Li; Shi-Jian Li; Xu-Ri Yao; Qing Zhao (Journal of Photochemistry and Photobiology B: Biology, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

Effects of cultivation on soil carbon and nitrogen along an altitudinal gradient in the Southeastern Tibetan Plateau - Haojing Lei; Fengzi Li; Xu-Ri; Songbo QU; Ribu Shama; Lin Zhang; Eryuan Liang (Forest Ecology and Management, 2025)

Characterization of intestinal bacteria for the production of quercetin and isoquercitrin from rutin - Narantsetseg Byambaakhuu; Shen Duan; Ren Sa; Qing-lan Yang; Hai-Yan Xu; Cheng-Bin Shan; Ri-hua Xu; Chao-Mei Ma (Archives of Microbiology, 2025)

Antimicrobial perylenequinones isolated from the endophytic fungus Alternaria alstroemeriae - Yong-Fu Li; Fang Yue; Xu-Ri Wan; Chang Li; Yi Sun; Yue-Hu Pei (Phytochemistry Letters, 2025)

Quantitative insights into osteocyte density developmental patterns in fossilized bone — A new method - Denis Horvath; Xu-Ri Wang; Martin Kundrát (Palaeoworld, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Evaluating waterbird migratory stopover habitat suitability in the Tumen River Estuary at the junction of China, North Korea and Russia using multi-source remote sensing imagery - Yang Liu; Jinhao Shi; Ri Jin; Weihong Zhu; Yue Guo; Baohua Guo; Xu Wang; Jingzhi Wang; Xiuxue Xia (Journal of Environmental Management, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

Anti-hyperlipidemia and anti-diabetic diarylheptanoids from the leaves of Aquilaria sinensis - Hong-Fang Cai; Kai-Wen Kang; Xu Gong; Xin-Yi Wu; Dong-Li Li; Jing-Wei Jin; Ri-Hui Wu; Li-She Gan (Phytochemistry Letters, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

A hybrid cloud detection and cloud phase classification algorithm using classic threshold-based tests and extra randomized tree model - Huazhe Shang; Husi Letu; Ri Xu; Lesi Wei; Laixiong Wu; Jiangqi Shao; Takashi M. Nagao; Takashi Y. Nakajima; Jérôme Riedi; Jie He; Liangfu Chen (Remote Sensing of Environment, 2024)

Five previously undescribed compounds from Ajuga lupulina Maxim. and their in vitro activities - Kun-Jun Wang; Te-Ri-Gen Bao; Yong-Cheng Yang; Dong-Dong Wang; An-Hua Wang; Xiao-Xu Gao; Ting Yan; Jing-Ming Jia (Natural Product Research, 2024)

Lipopolysaccharide alters VEGF-A secretion of mesenchymal stem cells via the integrin β3-PI3K-AKT pathway - Shuya Mei; Shaojie Qin; Ri Tang; Qiaoyi Xu; Yue Hu; Jinhua Feng; Zhengyu He; Yuan Gao; Hui Li; Shunpeng Xing (Molecular & Cellular Toxicology, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Extensive atmospheric methane consumption by alpine forests on Tibetan Plateau - Songbo Qu; Xu-Ri; Jiaoneng Yu; Almaz Borjigidai (Agricultural and Forest Meteorology, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Numerical simulation of the electromagnetic field in layered media applicable to high-frequency scenarios - Kun Li; Xu-Ri Huang; Kang Chen; Yun-Gui Xu; Wei-Ping Cao (Applied Geophysics, 2023)

Retrieval of cloud microphysical properties from Himawari-8/AHI infrared channels and its application in surface shortwave downward radiation estimation in the sun glint region - Gegen Tana; Xu Ri; Chong Shi; Run Ma; Husi Letu; Jian Xu; Jiancheng Shi (Remote Sensing of Environment, 2023)

Re-examination of Dashanpusaurus dongi (Sauropoda: Macronaria) supports an early Middle Jurassic global distribution of neosauropod dinosaurs - Xin-Xin Ren; Shan Jiang; Xu-Ri Wang; Guang-Zhao Peng; Yong Ye; Lei Jia; Hai-Lu You (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A general numerical method for solid particle erosion in gas–liquid two-phase flow pipelines - Ri Zhang; Kai Xu; Yong Liu; Haixiao Liu (Ocean Engineering, 2023)

Two new 2,5-diketopiperazine derivatives from mangrove-derived endophytic fungus Nigrospora camelliae-sinensis S30 - Dan-Yu Huang; Xu-Hua Nong; Yu-Qin Zhang; Wei Xu; Long-Yu Sun; Tao Zhang; Guang-Ying Chen; Chang-Ri Han (Natural Product Research, 2022)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Decadal change and inter-annual variability of net primary productivity on the Tibetan Plateau - Lan Cuo; Yongxin Zhang; Xu-Ri; Bingrong Zhou (Climate Dynamics, 2021)
Net primary productivity (NPP) is an important indicator of plant dynamics and the net carbon exchange between the terrestrial ecosystem and atmosphere. Both the long-term shifts in climate mean (climate change) and short-term variations around the climate mean (climate variability) have impacts on NPP but studies examining both aspects of climate variations are rare especially in the data-scarce regions such as the Tibetan Plateau (TP). Here, we used a dynamic vegetation model to investigate the impacts of the changes and variabilities in temperature, precipitation, cloud cover and CO 2 on NPP on the TP. The simulated NPP was evaluated using field and Moderate-Resolution Imaging Spectroradiometer NPP and was found to be reasonable. At monthly time scale, NPP significantly correlated concurrently and at 1-month lag with temperature, precipitation and cloud cover (coefficient of determination, R 2 , in 0.52–0.77). Annual NPP variability was high (low) where mean annual NPP was low (high). The effects of annual precipitation, cloud cover and temperature variability on annual NPP variability were spatially heterogeneous, and temperature variability appeared to be the dominant factor (R 2 of 0.74). Whereas, NPP changes were very similar to CO 2 increases across the TP (spatial correlation of 0.60), indicating that long-term changes in NPP were dominated by CO 2 increases. For both variability and long-term changes in NPP, temperature was the major factor of influence (highest spatial correlation of 0.67). These findings could assist in making informed mitigation policies on the impacts of climate change and variability on ecosystem and local nomadic communities.

Constitutive Modeling of Physical Properties of Coastal Sand during Tunneling Construction Disturbance - Jian-Feng Zhu; Hong-Yi Zhao; Ri-Qing Xu; Zhan-You Luo; Dong-Sheng Jeng (Journal of Marine Science and Engineering, 2021)
This paper presents a simple but workable constitutive model for the stress–strain relationship of sandy soil during the process of tunneling construction disturbance in coastal cities. The model was developed by linking the parameter K and internal angle φ of the Duncan–Chang model with the disturbed degree of sand, in which the effects of the initial void ratio on the strength deformation property of sands are considered using a unified disturbance function based on disturbed state concept theory. Three cases were analyzed to investigate the validity of the proposed constitutive model considering disturbance. After validation, the proposed constitutive model was further incorporated into a 3D finite element framework to predict the soil deformation caused by shield construction. It was found that the simulated results agreed well with the analytical solution, indicating that the developed numerical model with proposed constitutive relationship is capable of characterizing the mechanical properties of sand under tunneling construction disturbance.

Development and application of iterative facies-constrained seismic inversion - Huang Xu-Ri; Li Li; Li Fa-Lv; Li Xi-Sheng; Chen Qi; Dai Yue (Applied Geophysics, 2020)

Molecular epidemiology of enteroviruses associated with severe hand, foot and mouth disease in Shenzhen, China, 2014-2018 - Long Chen; Shao-Jian Xu; Xiang-Jie Yao; Hong Yang; Hai-Long Zhang; Jun Meng; Han-Ri Zeng; Xu-He Huang; Ren-Li Zhang; Ya-Qing He (Archives of Virology, 2020)

Marchenko imaging based on self-adaptive traveltime updating - Xiao-Chun Chen; Ye-Zheng Hu; Xu-Ri Huang; Hou-Zhu Zhang; Wei-Ping Cao; Yun-Gui Xu; Jing Tang (Applied Geophysics, 2020)

Zircon U–Pb ages and Hf isotopic compositions of two types of supracrustal rocks in the Northeastern Sulu UHP terrane: constraints on the surface boundary between South China and North China - Yang Xu; Ming-Ling Yang; Ali Polat; Kun-Guang Yang; Yuan-Ku Meng; Ri-Hui Li; Zhong-Bo Wang (International Geology Review, 2019)

Estimating N2O emissions from soils under natural vegetation in China - Xu-Ri; Yuesi Wang; Yinghong Wang; Haishan Niu; Yongwen Liu; Qianlai Zhuang (Plant and Soil, 2019)

Auxin, Cytokinin, and Ethylene Involved in Rice N Availability Improvement Caused by Endophyte Phomopsis liquidambari - Xin Li; Jun Zhou; Ri-Sheng Xu; Mei-Yao Meng; Xiao Yu; Chuan-Chao Dai (Journal of Plant Growth Regulation, 2018)

Improving Rice Ability to Degrade Different Polycyclic Aromatic Hydrocarbons Through Multigene Transformation of a Hybrid Dioxygenase System - Ri-He Peng; Biao Shi; Xiao-Yan Fu; Yong-Sheng Tian; Wei Zhao; Bo Zhu; Jing Xu; Hong-Juan Han; Zhong-Yi Yuan; Kai-Hong Liu; Quan-Hong Yao (Plant Molecular Biology Reporter, 2015)

Considerable methane uptake by alpine grasslands despite the cold climate: in situ measurements on the central Tibetan Plateau, 2008–2013 - Da Wei; Xu‐Ri; Tenzin‐Tarchen; Yuesi Wang; Yinghong Wang (Global Change Biology, 2015)
The uptake of CH 4 by aerate soil plays a secondary role in the removal of tropospheric CH 4 , but it is still highly uncertain in terms of its magnitude, spatial, and temporal variation. In an attempt to quantify the sink of the vast alpine grasslands (1 400 000 km 2 ) of the Tibetan Plateau, we conducted in situ measurements in an alpine steppe (4730 m) and alpine meadow (4900 m) using the static chamber and gas chromatograph method. For the alpine steppe, measurements (2008–2013) suggested that there is large interannual variability in CH 4 uptake, ranging from −48.8 to −95.8 μg CH 4 m −2 h −1 (averaged of −71.5 ± 2.5 μg CH 4 m −2 h −1 ), due to the variability in precipitation seasonality. The seasonal pattern of CH 4 uptakes in the form of stronger uptake in the early growing season and weaker uptake in the rainy season closely matched the precipitation seasonality and subsequent soil moisture variation. The relationships between alpine steppe CH 4 uptake and soil moisture/temperature are best depicted by a quadratic function and an exponential function ( Q 10 = 1.67) respectively. Our measurements also showed that the alpine meadow soil (average of −59.2 ± 3.7 μg CH 4 m −2 h −1 ) uptake less CH 4 than the alpine steppe and produces a similar seasonal pattern, which is negatively regulated by soil moisture. Our measurements quantified – at values far higher than those estimated by process‐based models – that both the alpine steppe and alpine meadow are considerable CH 4 sinks, despite the cold weather of this high‐altitude area. The consecutive measurements gathered in this study also highlight that precipitation seasonality tends to drive the interannual variation in CH 4 uptake, indicating that future study should be done to better characterize how CH 4 cycling might feedback to the more extreme climate.

The differentiation and development of pistils of hermaphrodites and pistillodes of males in androdioecious Osmanthus fragrans L. and implications for the evolution to androdioecy - Yi-Chun Xu; Li-Hua Zhou; Shao-Qing Hu; Ri-Ming Hao; Chong-jing Huang; Hong-Bo Zhao (Plant Systematics and Evolution, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Plant and soil responses of an alpine steppe on the Tibetan Plateau to multi-level nitrogen addition - Yongwen Liu; Xu-Ri; Xingliang Xu; Da Wei; Yinghong Wang; Yuesi Wang (Plant and Soil, 2013)

Characterization of microsatellites in white croaker (Pennahia argentata) through cross species amplification of Miichthys miiuy - DIAN QIAO SUN; TIAN JUN XU; RI XIN WANG (Journal of Genetics, 2013)

Fourteen polymorphic microsatellite markers isolated from big-head croaker (Collichthys lucidus) - DIAN-QIAO SUN; BO ZHANG; TIAN-JUN XU; RI-XIN WANG (Journal of Genetics, 2013)

Genetic diversity and population structure of the marbled rockfish, Sebastiscus marmoratus, revealed by SSR markers - DIAN-QIAO SUN; GE SHI; XUE-ZHU LIU; RI-XIN WANG; TIAN-JUN XU (Journal of Genetics, 2013)

Synthesis and potential antibacterial activity of new rhodanine-3-acetic acid derivatives - Jing Miao; Chang-Ji Zheng; Liang-Peng Sun; Ming-Xia Song; Li-Li Xu; Hu-Ri Piao (Medicinal Chemistry Research, 2013)

Wet precipitation chemistry at a high-altitude site (3,326 m a.s.l.) in the southeastern Tibetan Plateau - Bin Liu; Shichang Kang; Jimin Sun; Yulan Zhang; Ri Xu; Yongjie Wang; Yongwen Liu; Zhiyuan Cong (Environmental Science and Pollution Research, 2013)

Complementary screening, identification and application of a novel class II 5-enopyruvylshikimate-3-phosphate synthase from Bacillus cereus - Yong-Sheng Tian; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Quan-Hong Yao (World Journal of Microbiology and Biotechnology, 2013)

Responses of CO2, CH4 and N2O fluxes to livestock exclosure in an alpine steppe on the Tibetan Plateau, China - Da Wei; Xu -Ri; Yinghong Wang; Yuesi Wang; Yongwen Liu; Tandong Yao (Plant and Soil, 2012)

Phytoremediation and phytosensing of chemical contaminant, toluene: identification of the required target genes - Jian-Jie Gao; Xue-Fang Shen; Ri-He Peng; Bo Zhu; Jing Xu; Hong-juan Han; Quan-Hong Yao (Molecular Biology Reports, 2012)

Secretory expression and characterization of a soluble laccase from the Ganoderma lucidum strain 7071-9 in Pichia pastoris - Jing Sun; Ri-He Peng; Ai-Sheng Xiong; Yongsheng Tian; Wei Zhao; Hu Xu; Da-Tong Liu; Jian-Min Chen; Quan-Hong Yao (Molecular Biology Reports, 2012)

Analysis of gene expression profile of Arabidopsis genes under trichloroethylene stresses with the use of a full-length cDNA microarray - Bo Zhu; Ri-He Peng; Ai-Sheng Xiong; Xiao-Yan Fu; Wei Zhao; Yong-Sheng Tian; Xiao-Fen Jin; Yong Xue; Jing Xu; Hong-Juan Han; Chen Chen; Jian-Jie Gao; et al. (Molecular Biology Reports, 2012)

Development of an electrochemical immunoassay for detection of gatifloxacin in swine urine - Jian Yi; Meng Meng; Zhong-qiu Liu; Jin-fang Zhi; Yuan-yang Zhang; Jing Xu; Ya-bin Wang; Jin-ting Liu; Ri-mo Xi (Journal of Zhejiang University-SCIENCE B, 2012)

Sequence and expression analysis of cathepsin S gene in the miiuy croaker Miichthys miiuy - Yue-na Sun; Tian-jun Xu; Jian-xin Wang; Yuan-zhi Cheng; Ri-xin Wang (Fish Physiology and Biochemistry, 2011)

The complete mitochondrial genome of bighead croaker, Collichthys niveatus (Perciformes, Sciaenidae): structure of control region and phylogenetic considerations - Tian-jun Xu; Yuan-zhi Cheng; Yue-na Sun; Ge Shi; Ri-xin Wang (Molecular Biology Reports, 2011)

The myb transcription factor MdMYB6 suppresses anthocyanin biosynthesis in transgenic Arabidopsis - Jian-Jie Gao; Xue-Fang Shen; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jing Xu; Bo Zhu; Jian-Li Zheng; Quan-Hong Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Characterization of a Glucose-, Xylose-, Sucrose-, and d-Galactose-Stimulated β-Glucosidase from the Alkalophilic Bacterium Bacillus halodurans C-125 - Hu Xu; Ai-Sheng Xiong; Wei Zhao; Yong-Sheng Tian; Ri-He Peng; Jian-Min Chen; Quan-Hong Yao (Current Microbiology, 2011)

Semi-rational site-directed mutagenesis of phyI1s from Aspergillus niger 113 at two residue to improve its phytase activity - Yong-Sheng Tian; Ri-He Peng; Jing Xu; Wei Zhao; Feng Gao; Xiao-Yan Fu; Ai-Sheng Xiong; Quan-Hong Yao (Molecular Biology Reports, 2011)

Forced expression of Mdmyb10, a myb transcription factor gene from apple, enhances tolerance to osmotic stress in transgenic Arabidopsis - Jian-Jie Gao; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jing Xu; Bo Zhu; Quan-Hong Yao (Molecular Biology Reports, 2011)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

A First Set of Polymorphic Microsatellite Loci from the Marbled Rockfish, Sebastiscus marmoratus - Tian-jun Xu; Xian-qing Quan; Yue-na Sun; Kuang-ci Zhao; Ri-xin Wang (Biochemical Genetics, 2010)

Mutations in two amino acids in phyI1s from Aspergillus niger 113 improve its phytase activity - Yong-Sheng Tian; Ri-He Peng; Jing Xu; Wei Zhao; Feng Gao; Xiao-Yan Fu; Ai-Sheng Xiong; Quan-Hong Yao (World Journal of Microbiology and Biotechnology, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Cyanobacteria MT gene SmtA enhance zinc tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xi-Lin Hou; Quan-Hong Yao (Molecular Biology Reports, 2010)

Over-expression of ThpI from Choristoneura fumiferana enhances tolerance to cold in Arabidopsis - Bo Zhu; Ai-Sheng Xiong; Ri-He Peng; Jing Xu; Xiao-Fen Jin; Xiu-Rong Meng; Quan-Hong Yao (Molecular Biology Reports, 2010)

Terrestrial nitrogen cycle simulation with a dynamic global vegetation model - XU‐RI; I. C. PRENTICE (Global Change Biology, 2008)
A global scale Dynamic Nitrogen scheme (DyN) has been developed and incorporated into the Lund–Posdam–Jena (LPJ) dynamic global vegetation model (DGVM). The DyN is a comprehensive process‐based model of the cycling of N through and within terrestrial ecosystems, with fully interactive coupling to vegetation and C dynamics. The model represents the uptake, allocation and turnover of N in plants, and soil N transformations including mineralization, N 2 fixation, nitrification and denitrification, NH 3 volatilization, N leaching, and N 2 , N 2 O and NO production and emission. Modelled global patterns of site‐scale nitrogen fluxes and reservoirs are highly correlated to observations reported from different biomes. The simulation of site‐scale net primary production and soil carbon content was improved relative to the original LPJ, which lacked an interactive N cycle, especially in the temporal and boreal regions. Annual N uptake by global natural vegetation was simulated as 1.084 Pg N yr −1 , with lowest values −2 yr −1 (polar desert) and highest values in the range 24–36.5 g N m −2 yr −1 (tropical forests). Simulated global patterns of annual N uptake are consistent with previous model results by Melillo et al. The model estimates global total nitrogen storage potentials in vegetation (5.3 Pg N), litter (4.6 Pg N) and soil (≥67 Pg as organic N and 0.94 Pg as inorganic N). Simulated global patterns of soil N storage are consistent with the analysis by Post et al. although total simulated N storage is less. Deserts were simulated to store 460 Tg N (up to 0.262 kg N m −2 ) as NO 3 − , contributing 80% of the global total NO 3 − inventory of 580 Tg N. This model result is in agreement with the findings of a large NO 3 − pool beneath deserts. Globally, inorganic soil N is a small reservoir, comprising only 1.6% of the global soil N content to 1.5 m soil depth, but the ratio has a very high spatial variability and in hot desert regions, inorganic NO 3 − is estimated to be the dominant form of stored N in the soil.

Isolated and characterization of a cDNA encoding ethylene-responsive element binding protein (EREBP)/AP2-type protein, RCBF2, in Oryza sativa L. - Jin-Ge Liu; Zhen Zhang; Qiu-Lin Qin; Ri-He Peng; Ai-Sheng Xiong; Jian-Min Chen; Fang Xu; Hong Zhu; Quan-Hong Yao (Biotechnology Letters, 2006)

A comparison between measured and modeled N2O emissions from Inner Mongolian semi-arid grassland - Xu Ri; Yuesi Wang; Xunhua Zheng; Baomin Ji; Mingxing Wang (Plant and Soil, 2003)